Asuhan Kebidanan Komprehensif pada Ny. I Umur 27 Tahun dengan Riwayat SC di PMB Ny. S Wilayah Kerja Puskesmas Kaliwadas Tahun 2025 - Puspa Dwi Lestari; Endang Susilowati; Surni’ah Surni’ah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
High-risk pregnancy is a condition in which there is one or more dangerous factors such as a history of C-section. The incidence rate of pregnant women with a history of cesarean section at the Kaliwadas Community Health Center in 2024 is the lowest with a total of 0 cases compared to other cases (Kaliwadas Community Health Center Health Profile, 2024). The researcher's objective was to provide comprehensive midwifery care to pregnant women, women in labor, newborns, postpartum women, and families planning to have children using the Varney and SOAP midwifery management approaches. This study used a qualitative descriptive method with a case study approach, consisting of interviews, observations, physical and supporting examinations, documentation, medical records, maternal and child health (MCH) books, and other literature. The results showed that there were no problems in comprehensive midwifery care. Mrs. I gave birth via cesarean section because she had a history of previous cesarean sections and to prevent complications in the mother and baby. No problems were found in the care of the newborn and postpartum period. Mrs. I chose to use injectable contraception once every three months. From the results of the study, it can be concluded that the provision of comprehensive midwifery care is very important for maintaining the health of the mother and baby, so that early detection of a history of cesarean section can prevent possible complications.